THE STEPMOTHERS’ ROLE IN THE FAMILY AND THEIR QUALITIES - Nizomova Iroda Raxmon qizi (Web of Journals Publishing, 2024)
This article is about the stepmothers’ role in the family, their challenges, qualities and attitudes to their stepchildren. The image of the evil stepmother, a trope ingrained in our cultural consciousness, often overshadows the reality of what it means to be a stepmother. While the challenges are undeniable, the role of a stepmother is far more nuanced and multifaceted than the stereotypical portrayal suggests. They are often thrust into a pre-existing family dynamic, navigating a complex web of relationships and expectations. They are expected to instantly love and care for children who may not welcome them with open arms. The pressure to be a perfect mother figure, while simultaneously respecting the biological mother's role, can be overwhelming. They have to overcome some challenges in a new family, firstly, establishing a bond with stepchildren can be challenging. It takes time, patience, and understanding to earn their trust and respect. They must find a delicate balance between being involved and respecting the biological mother's role. Establishing clear boundaries is crucial to avoid conflict and ensure everyone feels comfortable. And also, stepmothers often face unrealistic expectations from both their partners and stepchildren. They are expected to be the perfect parent, without the benefit of years of shared history. Stepmothers are often judged by society, facing stereotypes and misconceptions. They may be seen as intruders or rivals, even if they are genuinely trying to build a loving family.
Keywords: Stepmother, challenges, their role, society, family.